P-N flame retardant as well as preparation method and application thereof

By constructing a water-insoluble P-N flame retardant in situ inside the wood, the problem that solid P-N flame retardant in the prior art is difficult to enter wood or easily permeable, and the efficient flame retardant and loss resistance of wood is achieved.

CN119462743AActive Publication Date: 2025-02-18HUNAN ACAD OF FORESTRY +1

Patent Information

Application Number
CN202411859982.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-02-18
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

Existing solid P-N flame retardants are difficult to enter the wood or are easily permeable, resulting in unstable flame retardant performance and poor loss resistance.

Method used

Water-soluble P-N flame retardant is constructed in situ in the wood by water-soluble precursors, using aminotrimethylenephosphonic acid and 1,3,5-tris(2-hydroxyethyl)1,3,5- The reaction of triazine-2,4,6-trione forms a phosphorus-containing and nitrogen-containing flame retardant precursor, and an acid-base reaction forms a water-insoluble P-N flame retardant.

Benefits of technology

It achieves efficient compatibility between P-N flame retardant and bio-based materials, imparts good flame retardant and loss resistance to wood, and has green and environmentally friendly preparation method, and has high flame retardant and smoke suppression efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462743A_ABST
    Figure CN119462743A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of flame-retardant materials, and particularly relates to a P-N flame retardant as well as a preparation method and application thereof. The preparation method of the P-N flame retardant comprises the following steps: (1) taking amino trimethylene phosphonic acid and adding a solvent for dilution; (2) adding 1, 3, 5-tri (2-ethoxyl) 1, 3, 5-triazine-2, 4, 6-triketone into the solution obtained in the step (1), and carrying out a constant-temperature oil bath reaction for 2-5 hours to obtain a P-N flame retardant precursor solution; (3) preparing an aqueous solution of an amino compound; and (4) dropwise adding the P-N flame retardant precursor solution into an aqueous solution of an amino compound, carrying out constant-temperature oil bath reaction for 5-10 minutes to generate white precipitates, continuing to react for 0.5-1 hour after the precipitates are generated, washing, carrying out suction filtration on the precipitates, and drying to obtain the P-N flame retardant. The P-N flame retardant disclosed by the invention is a white solid which is almost insoluble in water at normal temperature, and has a good flame retardant effect on a bio-based material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of flame retardant materials, and in particular relates to a PN flame retardant and a preparation method and application thereof. Background Art

[0002] Wood has been closely related to human life since ancient times. Wood has rich and beautiful texture and color, and has environmental characteristics that cannot be matched by building materials such as steel and concrete. The living environment composed of wood materials and their products can give people a comfortable natural feeling and unique aesthetic enjoyment. With the improvement of people's living standards and the pursuit of a better life, the use of wood products and wood materials in construction and home has increased dramatically. Wood is a flammable biomass material, so the potential fire hazards have also increased rapidly. The use of flame-retardant wood materials is one of the strategic measures to prevent and reduce fires. It has become an increasingly necessary research topic to flame-retardantly treat wood and wood materials to improve the combustion performance level of wood materials and reduce the incidence of fire.

[0003] There are many types of wood flame retardants. With the increase of people's environmental awareness, wood generally adopts safe, smoke-suppressing, non-toxic green flame retardants. Halogen-free flame retardants are the general trend. Therefore, the development of flame retardant systems such as phosphorus, nitrogen, boron, or phosphorus-nitrogen systems is the mainstream of wood flame retardants. Phosphorus and its compounds have a significant effect on the thermal decomposition process of oxygen-containing cellulose materials such as wood, mainly manifested in reducing the thermal decomposition temperature of wood, increasing the generation of charcoal, reducing the generation of combustible gases, and reducing heat release; for example, water-soluble ammonium polyphosphate (APP) is a high-efficiency wood flame retardant containing PN, but its disadvantage in the use process is that after APP enters the interior of the wood cells through the impregnation process, due to the hygroscopicity of APP, APP infiltrates into the wood surface, resulting in a decrease in the APP content inside the wood and a decrease in flame retardant properties.

[0004] Chinese patent CN104072759B discloses a PN series expansion reaction type flame retardant p-(carboxyphenyl-amino)-(carboxyphenyl-amideethyl)phenylphosphine oxide and its preparation method: (a) dissolving p-aminobenzoic acid in glacial acetic acid; (b) adding triethylamine and the mixed solution obtained in step a to a 2-carboxyethylphenyl hypophosphorous acid solution, stirring at high speed for 2 hours, heating to 80°C, reacting for 4 hours, and then cooling, hydrolyzing, filtering, washing with water, and drying to obtain a white powder, which is a PN series expansion reaction type flame retardant.

[0005] Chinese patent CN 112358453 A discloses a PNC type intumescent flame retardant and its preparation method and application in fire retardant coating. The preparation method of the intumescent flame retardant comprises: (1) dissolving trishydroxymethylaminomethane and sodium hydroxide in deionized water, adding the obtained mixed solution to an acetone solution of cyanuric chloride, and reacting in an ice bath; (2) adding sodium carbonate and p-hydroxybenzaldehyde to react, filtering, washing with water and drying; (3) adding a polyamine compound and the product of step (2) to ethanol, stirring and refluxing, evaporating the ethanol, washing with alcohol three times, and drying to obtain the product; (4) stirring the mixed solution of ethanol and water under a nitrogen atmosphere, adding APP and the product obtained in step (3), refluxing, detecting that no ammonia is released, filtering, washing with ethanol, washing with water, and drying. The method modifies all three components of the PNC type intumescent flame retardant, improves the water resistance of the PNC type intumescent flame retardant by chemical bonding, and can improve the water resistance of the fire retardant coating.

[0006] Chinese patent CN 114426701 B relates to the technical field of polymer flame retardant materials, and discloses the preparation of a PN compound synergistic graphene oxide flame retardant and its application in epoxy resin. First, under the protection of inert gas, p-aminoacetophenone, aniline, and p-toluenesulfonic acid are added to a three-necked flask and heated to melt, and then DOPO is added for magnetic stirring, and then filtered, washed and dried to obtain solid powder I; then graphene oxide is dispersed in an organic solvent, triethylamine and chlorinated compounds are added, and the reaction is heated in an oil bath. After the reaction is completed, the solid powder II is obtained by decompressing and filtering, washing and drying; finally, II is dispersed in an organic solvent, I and triethylamine are added, and the reaction is carried out by heating. After the reaction is completed, the product is filtered under reduced pressure and washed with ethanol and deionized water for multiple times, and then dried to obtain the product. The product is applied to the flame retardant research of epoxy resin curing system, and it is confirmed that it has excellent properties such as high efficiency flame retardancy, non-toxicity, and good compatibility.

[0007] The above three patents all involve the use of ethanol, glacial acetic acid, etc. as solvents or reaction media, or nitrogen protection, which undoubtedly increases the cost of solvent recovery, makes the process more complicated, and requires greater equipment investment, which increases the difficulty in industrial implementation.

[0008] It can be seen that phosphorus-nitrogen-based compounds are currently a class of flame retardant additives for polymer materials with promising applications, and are applied to polymer materials by means of physical blending. However, under normal circumstances, solid PN flame retardants are difficult to enter the interior of wood, or because of the characteristics of solubility, they will seep out to the surface of wood and cannot exert their flame retardant properties stably for a long time. Therefore, the technical problems regarding the compatibility and anti-loss performance of solid PN flame retardants in the current field still need to be solved urgently. Summary of the invention

[0009] The technical problem to be solved by the present invention is that wood flame retardants are easily soluble in water and easily lost, and the deficiencies and defects mentioned in the above background technology are overcome, and a PN flame retardant and a preparation method and application thereof are provided.

[0010] In order to solve the above technical problems, the technical solution proposed by the present invention is: A PN flame retardant, its chemical structure is: . The PN flame retardant of the present invention is a white solid that is almost insoluble in water at room temperature and has a good synergistic flame retardant effect on bio-based materials. Compared with conventional PN flame retardants that are difficult to enter the interior of bio-based materials or easily permeate, the PN flame retardant of the present invention that is poorly soluble in water can not only achieve high compatibility with bio-based materials, but also give wood flame retardancy and flame retardant anti-loss properties.

[0011] Under the same technical concept, the present application also provides a method for preparing a PN flame retardant, comprising the following steps: (1) Take aminotrimethylenephosphonic acid (ATMP), dilute it with a solvent, and stir it evenly; (2) adding 1,3,5-tris(2-hydroxyethyl)1,3,5-triazine-2,4,6-trione (THEIC) to the solution obtained by dilution in step (1), and reacting in a constant temperature oil bath to obtain a PN flame retardant precursor solution, wherein the molar ratio of aminotrimethylenephosphonic acid to 1,3,5-tris(2-hydroxyethyl)1,3,5-triazine-2,4,6-trione is 1:1 to 3:1; The phosphorus and nitrogen contents in the raw materials (ATMP) and (THEIC) are high, and the synthesized target product has a high phosphorus and nitrogen ratio, which is conducive to achieving the purpose of low-load and high flame retardancy of the flame retardant; since there are three hydroxyl groups in the 1,3,5-tris(2-hydroxyethyl)1,3,5-triazine-2,4,6-trione molecule, one hydroxyl group undergoes a dehydration esterification reaction with one phosphonate group, and one part of THEIC can react with one to three parts of ATMP to generate a PN flame retardant precursor containing a phosphonate group, and the PN flame retardant precursor is soluble in water; therefore, the molar ratio of aminotrimethylenephosphonic acid to 1,3,5-tris(2-hydroxyethyl)1,3,5-triazine-2,4,6-trione is controlled to be 1:1 to 3:1; (3) preparing an aqueous solution of an amino compound, wherein the molar ratio of the amino group to aminotrimethylenephosphonic acid in the amino compound is 1:1 to 3:1; (4) The PN flame retardant precursor solution in step (2) is added dropwise to the aqueous solution of the amino compound in step (3), and the reaction is carried out in a constant temperature oil bath. A white precipitate is generated after 5-10 minutes. The reaction is continued for 0.5-1 hour after the precipitate is generated, and then the precipitate is filtered and dried to obtain the PN flame retardant. The amino group reacts with the phosphonate in the PN flame retardant precursor solution to produce a salt, and further generates a water-insoluble PN flame retardant.

[0012] Preferably, the solvent in step (1) is water, and the concentration of the aminotrimethylenephosphonic acid after dilution is 20%-50%. The diluted aminotrimethylenephosphonic acid has a lower dilution concentration and a weaker acidity, which is conducive to the reaction.

[0013] Preferably, the reaction temperature of the constant temperature oil bath reaction in step (2) is 100-120° C., and the reaction time is 2-5 hours. At this temperature and reaction time, the reaction can be ensured to generate a PN flame retardant precursor containing phosphonate.

[0014] Preferably, the method for preparing the aqueous solution of the amino compound in step (3) is: adding the solid amino compound to water, heating and stirring at 95-105° C. for 1-2 hours, until the solid is completely dissolved to obtain a clear solution, and the aqueous solution of the amino compound is a saturated solution.

[0015] Preferably, the amino compound includes at least one of melamine, piperazine, guanine or 1-(2-aminoethyl)piperazine.

[0016] Taking melamine (MEL) as an example, the chemical reaction mechanism of the preparation process of this application is as follows:

[0017] During the preparation of N flame retardant, intermediates containing PN bonds are generated. Such PN bonds can increase the reactivity of fiber carbonyl and its phosphorylation rate, further increasing the carbonization rate. At the same time, nitrogen-containing compounds can release non-flammable gases such as ammonia, delay the volatilization loss of phosphorus compounds, and promote the protective effect of the phosphide carbon layer. Preferably, the constant temperature oil bath reaction temperature in step (4) is 100-105°C, and the reaction time is 0.5-1 h; the filtration is washed 1-3 times with 70-80°C hot water, and the drying temperature is 80-100°C.

[0018] Under the same technical concept, the present application also provides an application of a PN flame retardant in a flame retardant bio-based composite material, and the technology constructs the PN flame retardant in situ in the flame retardant bio-based composite material.

[0019] The present invention adopts a water-soluble precursor to construct a water-insoluble PN flame retardant in situ inside the wood, thereby imparting flame retardancy to the wood while resisting loss.

[0020] Preferably, the in-situ construction in the flame retardant bio-based composite material is specifically: (1) Preparation of bio-based materials; (2) Take aminotrimethylenephosphonic acid, dilute it with a solvent, and stir it evenly; (3) adding 1,3,5-tris(2-hydroxyethyl)1,3,5-triazine-2,4,6-trione to the solution obtained by dilution in step (1), and reacting in a constant temperature oil bath to obtain a PN flame retardant precursor solution, wherein the molar ratio of aminotrimethylenephosphonic acid to 1,3,5-tris(2-hydroxyethyl)1,3,5-triazine-2,4,6-trione is 1:1 to 3:1; and immersing the bio-based material in the PN flame retardant precursor solution; (4) preparing an aqueous solution of an amino compound, wherein the molar ratio of the amino group to aminotrimethylenephosphonic acid in the amino compound is 1:1 to 3:1; (5) The bio-based material treated in step (3) is further immersed in an aqueous solution of an amino compound and kept warm at 100-105° C. for 0.5-1 h. After the heat preservation is completed, the bio-based material is washed and dried to obtain a flame-retardant bio-based composite material with PN flame retardant constructed in situ in the bio-based material.

[0021] The flame retardant application scheme proposed in this aspect is to use a two-step impregnation method, in which the bio-based material is impregnated in the PN flame retardant precursor solution obtained in step (2) and the aqueous solution of the amino compound prepared in step (3), respectively. It is particularly noted that the solution in step (3) needs to be kept at 100-105°C for 0.5-1 h to ensure that the aqueous solution of the amino compound in step (3) enters the wood and reacts with the solution in step (2) impregnated in the bio-based material at 100-105°C, thereby in situ constructing the PN flame retardant in the cells of the bio-based material.

[0022] Preferably, the bio-based material comprises one or more of wood, bamboo, wood-bamboo derived plywood or reconstructed material; The washing comprises washing with deionized water for 1-3 times, the drying comprises drying at room temperature for 24-48 hours and then drying in an oven at 80-105°C for 24-48 hours, the impregnation adopts a bionic breathing impregnation method and an impregnation device, and the impregnation process specifically comprises: evacuating the impregnation device to below 0.2 MPa and maintaining it for 0.5-1 hour; then sucking the impregnation solution into the impregnation device with negative pressure, pressurizing the impregnation device to 1.0-1.2 MPa and maintaining it for 0.5-1.5 hours.

[0023] Compared with the prior art, the present invention has the following beneficial effects: (1) The PN flame retardant provided by the present invention contains two groups containing phosphorus and nitrogen. The phosphorus-containing component is decomposed into phosphoric acid, polyphosphoric acid or phosphoric anhydride when heated, so that the cellulose in the wood is phosphorylated and dehydrated to form carbon. Moreover, because the oxygen-containing acid of phosphorus is mostly viscous at high temperature, a liquid film (composed of Fig.12 The schematic diagram of the residual carbon of the sample treated with TAM can clearly show that it is beneficial to reduce the permeability of the carbon layer and protect the carbon layer from further oxidation. When the flame retardant contains both phosphorus and nitrogen, the interaction between nitrogen and phosphorus forms many intermediates containing PN bonds, which can increase the reaction activity of the cellulose carbonyl group and the phosphorylation rate. The nitrogen-containing group also has a nucleophilic effect on the ROP bond in the phosphide, so that the phosphorus is retained in the carbon layer in the form of a non-volatile salt, further improving the carbonization rate and the quality of the carbon layer, and giving the carbon layer excellent heat insulation and oxygen isolation capabilities. In addition to the synergistic solid phase flame retardant effect of P and N, the P and N composite flame retardant decomposes under heat to produce non-flammable gases such as NH3 and water vapor, which can dilute the air and play a role in gas phase flame retardancy. In addition, the composite flame retardant of phosphorus and nitrogen not only increases the flame retardant effect but also reduces the dosage. In Example 2 of the present application, the wood is impregnated with 1% of the PN flame retardant precursor solution in step (2) and 1% of the aqueous solution of the amino compound in step (3), and the limiting oxygen index (LOI) of the impregnated wood can exceed 32%, and the combustion grade reaches B1. (2) The preparation method of the PN flame retardant provided by the present invention is green and environmentally friendly, does not use toxic solvents, has high flame retardant and smoke suppression efficiency, and has low energy consumption. In addition, the scheme of first generating a soluble precursor and then generating an insoluble PN flame retardant is more conducive to the subsequent application of in-situ construction of PN flame retardants in bio-based materials; (3) The application of the PN flame retardant of the present invention can construct the PN flame retardant in situ in the cells of the bio-based material. On the one hand, the flame retardant obtained by in situ construction is insoluble in water and has good anti-loss performance. On the other hand, the unreacted phosphonate groups on the ATMP molecules can react with the hydroxyl groups on the cellulose of the bio-based material by hydrogen bonding or esterification to produce bonding, forming rivet points on the wood fibers to overcome the disadvantage that the flame retardant is easy to lose, thereby giving the wood material good flame retardant and smoke suppression properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1 is the chemical synthesis route of the PN flame retardant synthesized in Example 1; Figure 2 This is the FTIR analysis structure characterization spectrum of the PN flame retardant synthesized in Example 1; Figure 3 This is the XPS analysis structure characterization spectrum of the PN flame retardant synthesized in Example 1; Figure 4 The PN flame retardant synthesized in Example 1 1 H NMR analysis structural characterization spectrum; Figure 5 The PN flame retardant synthesized in Example 1 31 P NMR analysis structural characterization spectrum; Figure 6 This is the CONE result of the wood treated with the impregnation solution of Example 2; Figure 7 is the CONE result of the wood treated with the impregnation solution of Comparative Example 1; Figure 8 This is the CONE result of the wood treated with the impregnation solution of Comparative Example 2; Fig. 9 is the CONE result of the wood treated with the impregnation solution of Comparative Example 3; Fig.10 is the LOI result of the wood treated with the impregnation solution of Example 2; Fig.11 is the LOI result of the wood treated with the impregnation solution of Comparative Example 1; Fig.12 is the LOI result of the wood treated with the impregnation solution of Comparative Example 2; Fig.13 is the LOI result of the wood treated with the impregnation solution of Comparative Example 3; FIG14 is a digital photo and SEM image of carbon residue after cone calorimetry test of ordinary wood; 15 is a digital photo and SEM image of carbon residue after cone calorimetry test of wood treated with the solution in Example 2; FIG16 is a digital photo and SEM image of carbon residue after cone calorimetry test of wood treated with the solution in Comparative Example 1; 17 is a digital photo and SEM image of carbon residue after cone calorimetry test of wood treated with the stain solution in Comparative Example 2; FIG18 is a digital photo and SEM image of carbon residue after cone calorimetry test of wood treated with the stain solution in Comparative Example 3; Fig.19 is the LOI result of the wood treated with the impregnation solution of Example 3; Fig. 20 This is the LOI result of the wood treated with the impregnation solution of Comparative Example 4. DETAILED DESCRIPTION

[0026] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0027] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0028] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0029] Embodiment 1: This embodiment provides a PN flame retardant, whose chemical structure is shown below, and the chemical synthesis route is shown below Figure 1 As shown: ; The preparation method of the above PN flame retardant specifically comprises the following steps: (1) Take 400 mL of a 50% aqueous solution of aminotrimethylenephosphonic acid (ATMP) with a phosphorus content of 31.63%, dilute it with 400 mL of water, and stir evenly; (2) Weigh 76.62 g of 1,3,5-tris(2-hydroxyethyl)1,3,5-triazine-2,4,6-trione (THEIC), add the diluted solution obtained in step (1), react in a constant temperature oil bath at 120° C. for 4.0 h, and keep warm to obtain a PN flame retardant precursor solution; (3) Prepare a melamine (MEL) aqueous solution by adding 12.4 g of solid (MEL) into 450 mL of water and stirring at 100 °C for 1 h until the solid is completely dissolved to obtain a clear solution; (4) The PN flame retardant precursor solution was added dropwise to the MEL aqueous solution, heated and stirred at 100°C for 0.5 h, and a precipitate was produced. The stirring was continued for 0.5 h, and then the precipitate was filtered and washed three times with deionized water at 80°C, and dried at 80°C to obtain the PN flame retardant.

[0030] The structure of the obtained PN flame retardant (hereinafter referred to as TAM) was characterized by FTIR, XPS, 1 H NMR and 31 P NMR analysis of the chemical structure of TAM, the obtained characterization spectrum is as follows Figure 2-5 shown. Figure 2 The FTIR spectra of flame retardant TAM and its reactants are shown in Figure 1. -1The absorption signal at 1470 cm-1 is the stretching vibration of C=O caused by the vibration of the isocyanuric acid ring skeleton on the THEIC molecule. In addition to these characteristic peaks of the FTIR spectrum, the absorption signal at 1470 cm-1 corresponding to the NC=O of THEIC -1 The peak of MEL and the 1550cm corresponding to C=N -1 The peaks at 1510 cm -1 In the TAM spectrum, due to NH 4+ The tensile vibration and deformation vibration at 3120 cm -1 and 1400 cm -1 A new adsorption peak was found at 1250 cm -1 A new adsorption peak (P=O) was found at 3468 cm -1 and 3418 cm -1 The characteristic stretching peaks of -NH2 on MEL at 3350 cm-1 disappeared, which may be due to the formation of phosphate. -1 The broad adsorption peak of THEIC at 3370 cm -1 A small peak is formed at Figure 3 In the XPS, the prepared TAM showed absorption peaks of P and N, combined with the absorption peaks of C and O, indicating the presence of P and N elements in TAM, and the mass fraction ratio of C:O:N:P elements in the TAM flame retardant was 32.11%:26.45%:33.14%:8.30%. Figure 4 TAM shown 1 In the H NMR spectrum, the characteristic chemical shift values ​​of H1 and H2 were found to be 2.93 ppm and 3.26 ppm, corresponding to the two adjacent methylene groups of THEIC, respectively. The singlet signal at 7.50 ppm was attributed to the methylene H3 of ATMP. Figure 5 Solid state of TAM 31 P NMR spectrum. There are three strong singlet signals of phosphorus at 6.2, 9.8 and 11.0 ppm. The signal at 11.0 ppm (labeled a) can be attributed to the P atom of the C-PO(OH)2 group, while the peaks at 9.8 ppm (labeled b) and 6.2 ppm (labeled c) can be attributed to -P=O(O- NH 4+ )2 group and COP=O group. The corresponding peak area ratio is 1:0.85:1.1, which indicates that the molar ratio of MEL to THEIC to ATMP is 1:1.7:2.2. The results provide a basis for the successful synthesis of TAM and are consistent with the expected chemical structure.

[0031] Embodiment 2: This embodiment provides a PN flame retardant, whose chemical structure is shown below, and the chemical synthesis route is shown below Figure 1 As shown: ; This embodiment provides an application of a PN flame retardant in flame retardant of wood materials, which specifically includes the following steps: (1) Dry the Chinese fir sample in an oven at 105°C for 24 h until constant weight is reached, weigh it, and record the mass.

[0032] (2) Weigh 800 mL of a 50% aqueous solution of aminotrimethylenephosphonic acid (ATMP) with a phosphorus content of 31.63% and a mass of THEIC of 152.2 g, react at 120°C for 4 h, collect 900 mL of the reaction solution to obtain solution TA; take 40 mL of the solution TA prepared above, add 1960 mL of deionized water, stir evenly, and obtain a 1% TA solution; (3) Place the Chinese fir sample obtained in (1) into an impregnation tank, evacuate to 0.15 MPa, and maintain for 0.5 h; then use negative pressure to suck 2000 mL of 1% TA solution into the impregnation tank; next, pressurize the tank to 1.0 MPa and maintain it for 1 h using an air compressor. After depressurization, unload and discharge the solution from the impregnation tank, and take out the treated sample; (4) Weigh 50 g of MEL and add it to 2000 mL of water. Stir at 100 °C for 1 h until the solid is completely dissolved to obtain 2000 mL of MEL solution. Dilute the MEL solution to a 1% MEL solution. (5) Place the fir wood sample obtained in (3) into an impregnation tank, and follow the impregnation treatment process in step (3) to replace the 1% TA solution with the 1% MEL solution obtained in step (4), and keep the impregnation tank at 100 °C for 1 h. After depressurization, take out the treated sample, wash it with deionized water three times, dry it naturally at room temperature for 24 h, and then dry it in an oven at 105 °C for 48 h. Weigh it, record the mass, and obtain a 1% TAM / wood sample.

[0033] Embodiment 3: This embodiment provides a PN flame retardant, whose chemical structure is shown below, and the chemical synthesis route is shown below Figure 1 As shown: ; This embodiment provides an application of a PN flame retardant in the flame retardancy of fir wood, which specifically includes the following steps: (1) Dry the Chinese fir sample in an oven at 105°C for 24 h until constant weight is reached, weigh it, and record the mass.

[0034] (2) Take 800 mL of 50% aqueous solution of aminotrimethylenephosphonic acid (ATMP) with a phosphorus content of 31.63% and a mass of THEIC of 152.2 g, react at 120°C for 4 h, collect 900 mL of the reaction solution to obtain solution TA. Take 200 mL of the above prepared solution TA, add 1960 mL of deionized water, stir evenly, and obtain a 5% TA solution; (3) Place the Chinese fir sample obtained in (1) into an impregnation tank, evacuate to 0.15 MPa, and maintain for 0.5 h; then use negative pressure to suck 2000 mL of 5% TA solution into the impregnation tank; next, pressurize the tank to 1.0 MPa and maintain it for 1 h using an air compressor; after depressurization, unload and discharge the solution from the impregnation tank, and take out the treated sample; (4) Weigh 200 g of MEL and disperse it in 4000 mL of water. Stir at 100 °C for 1 h until the solid is completely dissolved to obtain 4000 mL of MEL solution. Dilute the MEL solution to a 5% MEL solution. (5) Place the fir wood sample obtained in (3) into an impregnation tank, and follow the impregnation treatment process in step (3) except that solution (2) is replaced with the 1% MEL solution obtained in step (4), and the impregnation tank is kept at 100°C for 1 h. After depressurization, take out the treated sample, wash it three times with deionized water, dry it naturally at room temperature for 24 h, and then dry it in an oven at 105°C for 48 h. Weigh it, record the mass, and obtain a 5% TAM / wood sample.

[0035] Embodiment 4: This embodiment provides a PN flame retardant, whose chemical structure is shown below, and the chemical synthesis route is shown below Figure 1 As shown: ; This embodiment provides an application of a PN flame retardant in the flame retardancy of a bamboo fiberboard, which specifically includes the following steps: (1) Take 3000 g of 200 mesh bamboo fiber sample and dry it in an oven at 70°C for 24 h until constant weight; (2) A TAM / bamboo powder composite material was prepared according to the experimental steps of Example 2, with the only difference being that in step (3), a 5% TA solution was firstly sucked into the impregnation tank, and then the corresponding bamboo powder was added, and the mixture was stirred at 100°C for 1 h; in step (5), a 5% MEL solution was firstly sucked into the impregnation tank, and then the corresponding bamboo powder was added, and the mixture was stirred at 100°C for 0.5-1 h; after depressurization, the treated sample was taken out, washed with deionized water for 3 times, naturally dried at room temperature for 24 h, and then dried in an oven at 105°C for 48 h, weighed, and the mass was recorded to obtain a 5% TAM / bamboo powder composite material; (3) Weigh the TAM / bamboo powder composite material obtained in (2), weigh 10% of the mass of the urea-formaldehyde resin adhesive of the TAM / bamboo powder composite material and mix them evenly with the 5% TAM / bamboo powder composite material obtained in (3), then place the TAM / bamboo powder composite material with the adhesive in an iron mold with a size of 300×300 mm and a thickness gauge of 1 cm, and hot press it for 8 min at 125°C and 1.2 MPa to obtain a flame retardant bamboo powder composite material treated with PN flame retardant.

[0036] Comparative Example 1: This comparative example provides an application of a melamine (MEL) flame retardant in flame retardant of wood materials, which specifically comprises the following steps: (1) Dry the Chinese fir sample in an oven at 105°C for 24 h until constant weight is reached, weigh it, and record the mass; (2) Weigh 50 g of MEL and add it into 2000 mL of water. Stir at a constant temperature of 100 °C until the solid is completely dissolved to prepare a MEL solution. Dilute the MEL solution to a 1% MEL solution. (3) The fir wood sample obtained in (1) was placed in an impregnation tank, and the impregnation treatment process in step (3) of Example 2 was followed, except that the 1% TA solution was replaced with the 1% MEL solution obtained in (2) above and added into the impregnation tank. After the pressure maintenance was completed, the pressure was released and the treated sample was taken out, washed with deionized water, naturally dried at room temperature for 24 h, and dried in an oven at 105°C for 48 h. The sample was weighed and the mass was recorded to obtain a 1% MEL / wood sample.

[0037] Comparative Example 2: This comparative example provides an application of an AM flame retardant in flame retardancy of wood materials, which specifically includes the following steps: (1) Dry the Chinese fir sample in an oven at 105°C for 24 h until constant weight is reached, weigh it, and record the mass; (2) Take 40 mL of ATMP solution and add it to 1960 mL of deionized water; (3) Place the Chinese fir sample obtained in (1) into an impregnation tank, evacuate to 0.15 MPa, and maintain for 0.5 h; then use negative pressure to suck 2000 mL of a solution (2) with a mass fraction of 1% ATMP into the impregnation tank; next, pressurize the tank to 1.0 MPa and maintain for 1 h; after depressurization, remove and discharge the ATMP solution from the impregnation tank, and take out the treated sample and place it naturally for use; (4) Take 11.09 g of MEL and add it to 2000 mL of deionized water, heat it to 100 °C and stir until a clear solution is obtained; (5) Place the fir sample obtained in (3) into an impregnation tank, evacuate to -0.15 MPa, and maintain for 0.5 h; then use negative pressure to suck 2000 mL of 1% MEL solution (4) into the impregnation tank; next, pressurize the tank to 1.0 MPa and maintain it for 1 h using an air compressor. After depressurization, unload and discharge the solution from the impregnation tank; (6) Take out the treated sample, wash it with deionized water, place it in a natural environment for 24 h, and then dry it in an oven at 105 °C for 48 h. Weigh it and record the mass to obtain the 1% AM / wood sample.

[0038] Comparative Example 3: This comparative example provides an application of a TA flame retardant in flame retardancy of wood materials, which specifically includes the following steps: (1) Dry the Chinese fir sample in an oven at 105°C for 24 h until constant weight is reached, weigh it, and record the weight; (2) The solution obtained in step (2) of Example 1 was used as the wood impregnation solution, and the wood was impregnated according to the same scheme as step (3) of Example 2. The sample was left to stand naturally at room temperature for 24 h, dried in an oven at 105°C for 48 h, weighed, and the mass was recorded. The obtained sample was a 1%TA / wood sample.

[0039] The combustion performance of the wood samples treated with the impregnation liquids of Example 2, Comparative Example 1, Comparative Example 2, and Comparative Example 3 was measured using a FTT cone calorimeter CONE and a JF-3 limiting oxygen index instrument, with ordinary wood as the blank control group. The obtained performance test results are shown in Table 1 and Figure 6-9 As shown: Table 1 Cone calorimetry test data of wood materials impregnated with different 1% impregnation solutions

[0040] Table 1 shows the cone calorimetry combustion performance test data of wood treated with different 1% impregnation solutions. From Table 1, we can see that the maximum heat release rate peak value of pure fir wood is 255.2kW / m 2 The average heat release rate, average effective combustion heat and total heat release are 94.1 kW / m 2 , 12.9 MJ / kg, 41.9 MJ / m 2 ; Total smoke release TSP is 10.7m 2 / m 2 The average heat release rate and total heat release of 1%TAM / wood with 1.0% new PN flame retardant TAM are 64.2 kW / m 2 , 25.4 MJ / m 2 , which is the lowest among all the impregnation treated samples, and is 29.9 kW / m lower than that of pure fir. 2, 16.5 MJ / m 2 Its total smoke volume is also the lowest among all samples, only 5.22 m 2 / m 2 , less than 1 / 2 of the total smoke produced by the log. Figure 3 It can be seen that the 1%TAM / wood sample is the first to extinguish and its flame burning time is the shortest. 1%TAM impregnation treatment of wood shows good flame retardant and smoke suppression effects.

[0041] Figure 10-13 The limiting oxygen index (LOI) results of Example 2 and Comparative Examples 1-3 were tested. Figure 4 It can be seen from the LOI of Chinese fir wood treated with different 1% impregnation liquids that the LOI of all impregnation-treated wood samples is higher than that of untreated Chinese fir by 17.4%, but the LOI of sample 1%TAM / wood is the highest, which is 34.2%, followed by 1%AM / wood, which is 33.5%; 1%TA / wood and 1%MEL / wood decrease in turn.

[0042] From the CONE and LOI experimental data, it can be seen that 1% TAM solution can effectively inhibit the heat release and smoke generation of wood, showing excellent flame retardant properties.

[0043] Figures 14-18 are digital photos and SEM images of the carbon residue after the cone calorimetry test of the wood treated with the impregnation liquid of Example 2 and Comparative Examples 1-3, with ordinary wood as the blank control group; wherein, Figure 14 (a) is a digital photo of the carbon residue after the cone calorimetry test of ordinary wood, Figure 14 (b) is the amount of carbon residue after the cone calorimetry test of ordinary wood, and Figure 14 (c) is the SEM image of the cone calorimetry test of ordinary wood; Figure 15 (a) is a digital photo of the carbon residue after the cone calorimetry test of the wood treated with the impregnation liquid, Figure 15 (b) is the amount of carbon residue after the cone calorimetry test of the wood treated with the impregnation liquid, and Figure 15 (c) is the SEM image of the cone calorimetry test of the wood treated with the impregnation liquid; the subsequent pictures are the same; in the figure, 1% A molten carbon layer is formed on the surface of the wood treated with TAM, which can effectively prevent oxygen and radiant heat in the air from entering the wood substrate under the carbon layer, reduce the rate of thermal decomposition of hydrocarbons such as cellulose, hemicellulose and lignin in the wood substrate to produce combustible gases, and reduce the intensity of wood combustion.

[0044] Comparative Example 4: This comparative example provides an application of an APP flame retardant in flame retardancy of wood materials, which specifically includes the following steps: (1) Dry the Chinese fir sample in an oven at 105°C for 24 h until constant weight is reached, weigh it, and record the mass.

[0045] (2) Weigh 105.3 g of APP and add it to 2000 mL of deionized water to prepare a 5% APP solution.

[0046] (3) Place the fir sample obtained in (1) into an impregnation tank, evacuate to 0.15 MPa, and maintain for 0.5 h. Then, use negative pressure to suck 2000 mL of a solution with a mass fraction of 5% APP into the impregnation tank. Next, pressurize the tank to 1.0 MPa and maintain it for 1 h using an air compressor. After depressurization, unload the solution from the impregnation tank and discharge it. Take out the treated sample.

[0047] (4) Take out the treated sample, wash it with deionized water, let it stand for 24 hours, and then dry it in an oven at 105°C for 48 hours. Weigh it and record the mass. The resulting sample is the 5% APP / wood specimen.

[0048] The combustion performance of the impregnated samples of Example 3 and Comparative Example 4 was measured using a FTT cone calorimeter CONE and a JF-3 limiting oxygen index instrument. The CONE combustion performance experimental data comparison is shown in Table 2.

[0049] Table 2 Cone calorimetry test data of 5% ATM and 5% APP impregnated fir

[0050] From the cone calorimetry test data of 5% TAM and 5% APP impregnated fir in Table 2, it can be seen that the ignition time of the fir sample treated with 5% TAM solution is 51 seconds later than that of pure fir. The heat release test parameter values ​​of the CONE test are significantly lower than those of pure fir. The total heat release is 12.32 MJ / m 2 , 29.55 MJ / m less than pure fir 2 , a decrease of 70.57%. PHRR and average heat release rate were 57.02% and 56.74% lower than those of pure fir, respectively. The total smoke release was 2.83 m 2 / m 2 , which is only 26.4% of pure fir. Compared with the fir sample impregnated with 5% APP solution in Comparative Example 4, except that the average heat release rate and the peak heat release rate are slightly higher than 5% APP / wood, the ignition time is delayed by 11 seconds, and the flame burning time is 56-360 s (average 304 s), which is shorter than 44-410 s (average 366 s); other factors such as the average effective combustion heat, total heat release, and total smoke production are all lower than 5% APP / wood, and the total heat release is 2.59 MJ / m lower than 5% APP / wood. 2The residual carbon rate is also 9 percentage points higher than that of the 5% APP sample; and TAM is more effective in suppressing smoke release than APP, with its total smoke production less than one-third of pure fir, and only 64.9% of 5% APP / wood. It can be seen that TAM is an excellent flame retardant for wood materials, which has the same high efficiency as APP in suppressing wood combustion and reducing heat release, and has a better smoke suppression effect than APP.

[0051] Fig.19 , 20 The limiting oxygen index (LOI) test results in Example 3 and Comparative Example 4 were tested. Figure 6 It can be seen that the limiting oxygen index LOI of pure fir is 17.4%, the LOI of 5% APP / wood sample treated with 5% APP impregnation liquid is 32.1%, and the LOI of 5% TAM / wood sample treated with 5% ATM impregnation liquid is as high as 48.4%, which is 50.78% higher than 5% APP / wood. TAM has good flame retardant properties.

[0052] Comparative Example 5: This comparative example provides a common bamboo fiberboard, and the preparation method of the bamboo fiberboard is as follows: (1) After the bamboo fiber sample is passed through a 200-mesh sieve, 500 g of the bamboo fiber sample is dried in an oven at 70°C for 24 h until constant weight is reached.

[0053] (2) Weigh 10% of the mass of the bamboo fiber as urea-formaldehyde resin adhesive and mix evenly with the bamboo fiber obtained by drying in (1), and hot press at 125°C and 1.2 MPa for 8 min to form the mixture.

[0054] The oxygen index of the bamboo fiberboard obtained in Example 4 and Comparative Example 5 was measured by using a FTT cone calorimeter CONE and a JF-3 limiting oxygen index instrument, and the results are listed in Table 3. From the data in the table, it can be seen that as the content of TAM increases, the LOI of the bamboo fiberboard increases. The LOI of the 20% TAM flame retardant fiberboard is as high as 60.8%, indicating that TAM has excellent flame retardancy.

[0055] Table 3 Limiting oxygen index of different TAM flame retardant bamboo fiberboards

Claims

1. A PN flame retardant, characterized in that: Its chemical structure is: 。 2. A method for preparing a PN flame retardant, characterized in that: The following steps are involved: (1) Take aminotrimethylenephosphonic acid, dilute it with a solvent, and stir it evenly; (2) adding 1,3,5-tris(2-hydroxyethyl)1,3,5-triazine-2,4,6-trione to the solution obtained by dilution in step (1), and reacting in a constant temperature oil bath to obtain a PN flame retardant precursor solution, wherein the molar ratio of aminotrimethylenephosphonic acid to 1,3,5-tris(2-hydroxyethyl)1,3,5-triazine-2,4,6-trione is 1:1 to 3:1; (3) preparing an aqueous solution of an amino compound, wherein the molar ratio of the amino group to aminotrimethylenephosphonic acid in the amino compound is 1:1 to 3:1; (4) The PN flame retardant precursor solution in step (2) is added dropwise to the aqueous solution of the amino compound in step (3) for constant temperature oil bath reaction. A white precipitate is generated after 5-10 minutes. The reaction is continued for 0.5-1 hour after the precipitate is generated. The precipitate is then filtered and dried to obtain the PN flame retardant.

3. The preparation method according to claim 2, characterized in that: The solvent in step (1) is water, and the concentration of the aminotrimethylenephosphonic acid after dilution is 20%-50%.

4. The preparation method according to claim 2, characterized in that: The reaction temperature of the constant temperature oil bath reaction in step (2) is 100-120°C, and the reaction time is 2-5h.

5. The preparation method according to claim 2, characterized in that: The method for preparing the aqueous solution of the amino compound in step (3) is: adding the solid amino compound to water, heating and stirring at 95-105° C. for 1-2 hours, until the solid is completely dissolved to obtain a clear solution, wherein the aqueous solution of the amino compound is a saturated solution.

6. The preparation method according to claim 5, characterized in that: The amino compound includes at least one of melamine, piperazine, guanine or 1-(2-aminoethyl)piperazine.

7. The preparation method according to claim 2, characterized in that: The temperature of the constant temperature oil bath reaction in step (4) is 100-105°C, and the reaction time is 0.5-1h; during the filtration, the product is washed 1-3 times with hot water at 70-80°C, and the drying temperature is 80-100°C.

8. Use of the PN flame retardant according to claim 1 or the PN flame retardant obtained by the preparation method of the PN flame retardant according to any one of claims 2 to 7 in flame-retardant bio-based composite materials, characterized in that: A PN flame retardant is constructed in situ in the flame retardant bio-based composite material.

9. The use according to claim 8, characterized in that The in-situ construction in the flame retardant bio-based composite material is specifically as follows: (1) Preparation of bio-based materials; (2) Take aminotrimethylenephosphonic acid, dilute it with a solvent, and stir it evenly; (3) adding 1,3,5-tris(2-hydroxyethyl)1,3,5-triazine-2,4,6-trione to the solution obtained by dilution in step (1), and reacting in a constant temperature oil bath to obtain a PN flame retardant precursor solution, wherein the molar ratio of aminotrimethylenephosphonic acid to 1,3,5-tris(2-hydroxyethyl)1,3,5-triazine-2,4,6-trione is 1:1 to 3:1; and immersing the bio-based material in the PN flame retardant precursor solution; (4) preparing an aqueous solution of an amino compound, wherein the molar ratio of the amino group to aminotrimethylenephosphonic acid in the amino compound is 1:1 to 3:1; (5) The bio-based material treated in step (3) is further immersed in an aqueous solution of an amino compound and kept warm at 100-105° C. for 0.5-1 h. After the heat preservation is completed, the bio-based material is washed and dried to obtain a flame-retardant bio-based composite material with PN flame retardant constructed in situ in the bio-based material.

10. The use according to claim 9, characterized in that The bio-based material includes one or more of wood, bamboo, wood-bamboo derived plywood or reconstructed material; The washing includes washing with deionized water for 1-3 times, and the drying includes drying at room temperature for 24-48 hours and then drying in an oven at 80-105° C. for 24-48 hours; The impregnation is a bionic breathing impregnation method, using an impregnation device, and the impregnation process specifically includes: evacuating the impregnation device to below 0.2 MPa and maintaining it for 0.5-1 h; then using negative pressure to suck the impregnation solution into the impregnation device, pressurizing the impregnation device to 1.0 ~1.2 MPa and maintaining it for 0.5-1.5 h.

Citation Information

Patent Citations

  • A P-N series expansion reaction type flame retardant and its preparation method

    CN104072759B

  • P-N-C type intumescent flame retardant and preparation method and application thereof in fireproof coating

    CN112358453A

  • Preparation of a PN compound synergistic graphene oxide flame retardant and its application in epoxy resins

    CN114426701B

  • P-N expanded reaction type flame retardant and preparation method thereof

    CN104072759A

  • Novel organic phosphorus-nitrogen flame retardant as well as preparation method and application thereof

    CN105153228A

Cited By

  • Flame retardant, flame-retardant polyvinyl alcohol and preparation method of flame-retardant polyvinyl alcohol

    CN120665423A